Zero‐bias elimination with selective non‐commensurate sampling for PN code tracking. Issue 3 (20th February 2020) - Ma, Chunjiang; Ni, Shaojie; Tang, Xiaomei; Xiao, Zhibin; Sun, Guangfu
Abstract : Zero bias is the main source of error in high‐precision applications based on pseudo‐noise (PN) ranging. This study proposes a selective non‐commensurate sampling frequency design method applied to the digital code‐tracking loop which can effectively suppress the code‐phase zero bias caused by incomplete sampling of the spread spectrum signal. The maximum (MAX) and standard deviation (STD) of the zero bias independent of code and the initial phase are used to design the sampling frequency. The code correlation reference waveform is utilised to establish a statistical analysis model of the digital discriminator zero bias. Analytical expressions of the zero‐bias MAX and STD are derived. The performance of the proposed method is assessed as per code Doppler, binary offset modulation, and thermal noise. Fibre optic time synchronisation equipment is used to determine the feasibility of eliminating PN code‐tracking zero bias based on selective non‐commensurate sampling.